Relative growth of carcass tissues of goat kids from five breed types finished on pasture or feedlot - Lourençon, Raquel Vasconcelos [UNESP]; Gonçalves, Heraldo Cesar [UNESP]; De Lima Meirelles, Paulo Roberto [UNESP]; Browning, Richard; Leite-Browning, Maria Lenira; Chávari, Andréia Cristina Toniolo [UNESP]; Marques, Raquel Ornelas [UNESP]; Canizares, Gil Ignacio Lara [UNESP]; Leal, Natalia Santos [UNESP]; Gomes, Helen Fernanda Barros (Universidade Estadual de Londrina, 2016)
The aim of this study was to evaluate the effect of cross breeding, finishing system, and gender on the relative growth of carcass tissues of dairy kids. Seventy eight kids (39 male and 39 female) from five breed types were used: Alpine; 1/2 Boer + 1/2 Alpine (1/2 BA); 1/2 Nubian + 1/2 Alpine (1/2 ANA); 3/4 Boer + 1/4 Alpine (3/4 BA); and 1/2 Nubian + 1/4 Boer + 1/4 Alpine (TC). Kids were distributed into two finishing systems: in pasture with doe (FS1) and weaned in feedlot (FS2). Kids were slaughtered at a mean age of 128.4 ± 7.9 days and mean live weight of 22.07 kg. The mean weight of half carcasses was 5.09 kg. To determine allometric growth, we used the exponential equation Y= aXb. In the half carcass, muscle tissue showed comparatively early growth in group 1/2 BA, whereas fat tissue of animals in FS1 had relatively late growth. Females exhibited early growth of muscle tissue, while in males this tissue was intermediate. The 1/2 BA first-cross improved carcass characteristics by enhancing the growth of muscle tissue.
Keywords: Allometry; Alpine; Boer; Finishing system; Nubian